2012
DOI: 10.1002/pds.3348
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for the detection of adverse drug reactions: comparison of hospital databases, chart review and spontaneous reporting

Abstract: Although not frequently used, the detection of ADRs through databases is a relatively less expensive, fast and effective methodology that can improve current pharmacovigilance systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
(22 reference statements)
1
29
0
1
Order By: Relevance
“…Nevertheless, we believed that the detection rate in our study may still under-estimated due to under-recognition and under-reporting of ADRs in routine hospital activity. However, when compared with the spontaneous report, our study confirmed that administrative database yields higher detection rate of ADRs than spontaneous report 9 . In this study, about 286 % increase in incidence of ADR-related hospital admission was detected when using administrative database (2.74 %), as compared to spontaneous report (0.71%).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Nevertheless, we believed that the detection rate in our study may still under-estimated due to under-recognition and under-reporting of ADRs in routine hospital activity. However, when compared with the spontaneous report, our study confirmed that administrative database yields higher detection rate of ADRs than spontaneous report 9 . In this study, about 286 % increase in incidence of ADR-related hospital admission was detected when using administrative database (2.74 %), as compared to spontaneous report (0.71%).…”
Section: Discussionsupporting
confidence: 75%
“…Pharm Sci Asia 2017; 44 (3), [142][143][144][145][146][147][148][149][150][151][152][153] rates for ADRs than analysis of database and spontaneous reporting [6][7][8][9] . Nevertheless, medical chart review and intensive monitoring require high resource and technical intensive.…”
Section: Original Articlementioning
confidence: 99%
“…Pharmacovigilance centres play a major role in the postmarketing monitoring of drug safety, which, in many countries, is based on spontaneous (or voluntary) reporting [7]. Clinical observations, from both patients and healthcare professionals, serve as a starting point for reporting suspected ADRs.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical observations, from both patients and healthcare professionals, serve as a starting point for reporting suspected ADRs. Most reported suspected ADRs are reported by health professionals, but also by patients [7], which means that health professionals should have sufficient knowledge, adequate abilities, and a positive attitude to evaluating and reporting possible ADRs encountered in daily practice. They are encouraged, and in some countries legally obliged, to report serious and unknown ADRs to the competent authority [8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation